IDENTIFIKASI KONDISI DAN UPAYA PENGUATAN PENGAWASAN DALAM RANGKA REFORMASI BIROKRSI DI KABUPATEN PEKALONGAN - Herbasuki Herbasuki (GEMA PUBLICA : Jurnal Manajemen dan Kebijakan Publik, 2015)
Supervision is one of the areas of bureaucarcy reform that is expected toincrease in clean governance and free of corruption, collusion and nepotism(KKN). The purpose of the study was to identify the internal oversight authority,issues and efforts to strengthen the government which’s done by PekalonganRegency. The study was conducted with a qualitative descriptive approach.Supervisory authority pursue by the rules of Pekalongan Regency No. 56 of2013 which includes monitoring the implementation of government affairs at thedistrict level, village government affairs, internal control implementation of thetasks and functions performed by the Inspectorate.The problems encountered by the activities of the budgeted plan in theplanning documents, the quantity and quality of auditors is still lacking,unfavorable employment policy, the lack of budget and unstandard of operationalproject.Efforts must be made in order to strengthen the supervision such ascommitment and exemplary leadership, gradual addition of auditor, the additionof operational funds and increase the quality of personnel SPIP (Internal ControlSystem of the Government) in a planning manner in order to assist theinspectorate and prevent acts of maladministration and fraud (irregularities) ingovernance.Keywords: supervision; bureaucracy reforms